Preparation and properties of monolithic Bi2WO6/graphene aerogel - CHANG Wei; GU Xiaoqi; LEI Chao; GENG Qian; FAN Jiangtao (Xi'an Gongcheng Daxue xuebao)
In order to obtain the retrievable photocatalytic material, the monolithic Bi2WO6/graphene aerogel was successfully prepared by solvothermal method combined with freeze-drying. The materials were characterized by SEM, XRD, FT-IR and UV-Vis. The effects of different hydrothermal temperatures on the morphology, structure and properties of Bi2WO6/graphene aerogel were investigated. The results show that when the hydrothermal temperature is 120 ℃, the material has good integrity; and when the hydrothermal temperature is 110 ℃, the material has good photocatalytic activity. The degradation rate of Rhodamine B can reach 99.7% after 120 min illumination with 500 W xenon lamp.